Relationship between management practices, fungal infection and aflatoxin for stored maize in Benin - Hell, K.; Cardwell, K.F.; Poehling, H.M. (Wiley, 2003)
This study relates preharvest and harvest practises to postharvest quality of maize in Benin, West Africa. Fungal infection and aflatoxin levels were evaluated in 300 farmers’ stores in four agro‐ecological zones over 2 years (1993–1995), at the beginning of storage (sample A) and 6 months later (sample B). Aspergillus flavus infected 10–20% of the kernels in sample A (1993–1994). In sample B, 54–79% of the kernels were infected with A. flavus. In 1994–1995, A. flavus infection was higher in sample A (27–47%) than B (8–26%). Fusarium species were found in 38–58% of the kernels in sample A in both years, but decreased slightly to 29–51% in sample B. Significant agroecozonal effects existed within sampling, but were not consistent between samplings and years. Of the total number of samples collected (744), 38.8% were found to be aflatoxin‐positive, with an average of 105 parts per billion (ppb) and 60% of the aflatoxin‐positive samples having a contamination approximately 20 ppb, the intervention level recommended by the World Health Organization. Factors associated with increased aflatoxin were: planting local maize varieties in southern Benin, intercropping with cowpea, groundnut, or cassava, use of urea‐fertilizer, damage to maize in the field, prolonged harvesting, long drying periods in the field, and winnowing. Practices that reduced aflatoxin contamination were: planting improved varieties in northern Benin, mixed cropping with vegetables, use of NPK‐fertilizer, drying of harvested cobs for 60–90 days, drying ears without the husk, sorting out of poor quality ears.